Combination therapy for patients with a developmental dysphasia: selected approaches based on special education, rehabilitation and psychology in a systematic case study - Vostrý, Michal; Pešatová, Ilona; Lanková, Barbora; Fleischmann, Otakar; Jelínková, Jaroslava; Štolová, Ivana; Beranová, Radka; Mundoková, Nikola (Neuro-endocrinology letters, 2023)
OBJECTIVE: The paper deals with the possibilities of the development and the support of individuals with developmental dysphasia with regard to the legislative framework of the Czech Republic in the field of education and presents the results of a systematic case study of a child patient diagnosed with developmental dysphasia (according to ICD-10; F80.1 and F80.2). CASE REPORT: The study aimed to determine the effect of combined therapy using long-term special educational, rehabilitation and psychological intervention, speech therapy and music therapy on the development of the patient's communication skills. The proband was selected by random, stratified sampling based on pre-determined relevant characteristics (age 6 years i.e., before entering primary school, diagnosed with developmental dysphasia). A 6-year-old child patient participated in the research with the consent of the legal representative. The therapy was focused on special educational care, speech therapy, music therapy and psychological intervention (including psychotherapy). During the hospitalization and post-hospitalization care, there was also the presence of a physiotherapist and an occupational therapist. CONCLUSION: The results of the research point out the need for regular and close multidisciplinary cooperation of an occupational therapist, a physiotherapist, a special educator, a speech therapist, a music therapist and a psychologist when working with patients diagnosed with developmental dysphasia. These professions focus specifically on specific areas of support with a focus on cognitive, phatic and motor functions with the support of social adaptability.
Keywords: Child; Education, Special; speciální vzdělávání; Aphasia; Humans; Česká republika; lidé; dítě; afázie; Czech Republic